Stability Study of Ipomoea reptans Extract Self-Nanoemulsifying Drug Delivery System (SNEDDS) as Anti-Diabetic Therapy - Pinus Jumaryatno, Lutfi Chabib & , Farida Hayati, Rizki Awaluddin (Journal of Applied Pharmaceutical Science, 2018)
Diabetes mellitus (DM) is one of the metabolic syndromes that is characterized by the excessive accumulation of blood glucose, also called as hyperglycemia, and carbohydrate, fat, and protein metabolism disorder. The antioxidant compounds on Ipomoea reptans possess the pharmacological activity of DM with low absorption in the systemic circulation. Stability is one of the factors that affect the safety, quality, and efficacy of the SNEDDS (Self- Nanoemulsifying Drug Delivery) dosage form. This study aimed to evaluate the stability of Ipomoea reptans leaf extract (IPE) SNEDDS. The IPE SNEDDS was made using capryol 90 as the oil phase, tween 20 as surfactants, and polyethylene glycol (PEG) 400 as the cosurfactant. The stability study was conducted with several physical stability tests, which were centrifugation test, heating-cooling cycle test, and freeze-thaw cycle test. The result indicated that the particle size of the IPE SNEDDS was ≤100 nm and indicated good physical stability. It can be concluded that the IPE SNEDDS possesses good stability profile.
Keywords: Ipomoea reptans, SNEDDS,Stability, Capryol 90,Diabetes Mellitus.